2007
DOI: 10.1152/ajpendo.00693.2006
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-induced Ca2+ release increases AMPK-dependent glucose uptake in rodent soleus muscle

Abstract: EA. Caffeine-induced Ca 2ϩ release increases AMPK-dependent glucose uptake in rodent soleus muscle. Am J Physiol Endocrinol Metab 293: E286-E292, 2007. First published April 3, 2007; doi:10.1152/ajpendo.00693.2006.-Previous studies have proposed that caffeine-induced activation of glucose transport in skeletal muscle is independent of AMP-activated protein kinase (AMPK) because ␣-AMPK Thr172 phosphorylation was not increased by caffeine. However, our previous studies, as well as the present, show that AMPK ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
140
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 37 publications
(61 reference statements)
12
140
3
1
Order By: Relevance
“…Although glucose uptake was lower with caffeine treatment in the DN mice, there continued to be elevated glucose uptake rates over resting conditions. This increase in glucose uptake supports the notion that glucose uptake is regulated by Ca 2ϩ signaling intermediates that are independent of AMPK activation (22,53). Our results further suggest that AMPK␣ 2 activation may be more critical to the regulation of glucose metabolism during states of increased intracellular [Ca 2ϩ ] induced by caffeine than to the regulation of FA metabolism in skeletal muscle.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although glucose uptake was lower with caffeine treatment in the DN mice, there continued to be elevated glucose uptake rates over resting conditions. This increase in glucose uptake supports the notion that glucose uptake is regulated by Ca 2ϩ signaling intermediates that are independent of AMPK activation (22,53). Our results further suggest that AMPK␣ 2 activation may be more critical to the regulation of glucose metabolism during states of increased intracellular [Ca 2ϩ ] induced by caffeine than to the regulation of FA metabolism in skeletal muscle.…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown by us and others that caffeine-induced increases in Ca 2ϩ signaling regulate substrate metabolism, possibly via AMPK activation (1,6,22,35). Indeed, we have shown that when CaMKII or CaMKK was inhibited during caffeine stimulation, there were subsequent decreases in AMPK␣ 2 activity along with decreases in the rates of FA uptake, glucose uptake, and FA oxidation (1,35).…”
Section: Discussionmentioning
confidence: 58%
“…While our results do not support a role for AMPK in caffeine-induced glucose transport, Jensen et al (20) recently reported that AMPK is causally linked to the caffeinestimulated glucose uptake response. These workers provide evidence to demonstrate that caffeine exerts an isoform-specific increase in AMPK ␣ 1 activity and acetyl-CoA carboxylase (ACC)␤ phosphorylation in the absence of total AMPK Thr172 phosphorylation (20). Accordingly, they propose that investigations that have only measured total AMPK Thr172 phosphorylation may be prone to type 2 errors and have resulted in false conclusions with regard to the effect of caffeine on AMPK activation.…”
contrasting
confidence: 99%
“…However, supplementation of the diet with cocoa powder extract has been suggested to reduce blood glucose concentration in STZ-induced diabetes in rats [24]. Caffeine is known to increase the glucose transport rate in the absence of insulin in rodent skeletal muscles [25,26]. Also, caffeine activates cyclic AMP-dependent protein kinase through an insulin-independent mechanism, which increases AMP kinase-1 to promote glucose transport.…”
Section: Discussionmentioning
confidence: 99%